Eficiência na oferta de serviços de saúdo no estado de São Paulo: uma análise comparativa entre municípios selecionados - Passoni, Pedro Felipe Mascarin (Universidade Federal de São Carlos, 2014)
Assess levels of efficiency in the provision of public services and its determinants becomes increasingly important to meet growing needs of the population and the scarcity of resources. The provision of health services accounts for a large part of municipal budgets and fundamentally depends on a good management of limited public resources, as well as greatly impacting on social and economic development of municipalities. In this sense, the present study sought to examine the level of efficiency in the delivery of public health services to the population of the municipalities of the state of São Paulo to promote wellness. So it was posed a mathematical programming problem involving the measurements of efficiency, through the non-parametric efficiency analysis technique known as Data Envelopment Analysis (DEA), with varying scale and orientation product returns. The results indicate that the municipalities of the state of São Paulo have unsatisfactory utilization of resource allocation for the provision of public health services. In general, districts that spend more did not show higher levels of efficiency, but for the group of the least efficient municipalities this hypothesis was confirmed. Regarding the relationship with the Municipal Human Development Index (IDH-M), a slightly negative relationship was found. On the other hand, the group of 14 less efficient shows a positive relationship between the score and the IDH-M. The results are scattered so apparently random state, and indicate that there is no homogeneity among municipalities. Observe also that there are municipalities that although efficient, spend resources for health that are lower than seems appropriate. All this demonstrates the asymmetry and how unequal is the situation of municipalities in the state of São Paulo in relation to health services. Furthermore, the group of the most efficient is less populated, compared to less efficient. According to the scale of production, the municipalities are presented as most in descending scale. The biggest problem has been found in the municipalities of scale. Regarding projections for municipalities become efficient, the results showed that the inefficient municipalities require increases of 124,66 % on average in their health services. Among regions the differences are not very striking, but there is a slight predominance of efficient municipalities focusing on the West region of the state. The Administrative Regions (RA's) showed similar mean technical efficiency, showing that no state in a spatial distribution pattern efficiency. The relationship between efficiency scores of RA's and IDH-M of each was positive. With this, one realizes that the average level of efficiency tends to increase when the IDH-M in each RA increases. It is, therefore, required a revision of management practices in counties in order to improve the methods adopted to make better use of resources and can provide the population with the best provision of their basic needs and more effective action by the executive branch.
Efficiency in the provision of health services in the state of São Paulo: a comparative analysis between the selected cities
Keywords: eficiência; gasto público; análise envoltória de dados; serviços de saúde; municípios paulistas; despesa pública; eficiência organizacional; efficiency; public spending; data envelopment analysis; health services; municipalities of São Paulo; CIENCIAS SOCIAIS APLICADAS::ECONOMIA